Brand Awareness pada Warung Kopi Imah Babaturan - Pandu Dewantara; Indri Rachmawati (UNISBA Press, 2023)
runs out with time, this is because eating and drinking are primary needs for every human being on earth in order to maintain survival. To create public interest in getting to know and buying a product, a brand conducts digital marketing communications to increase its brand awareness. This research will discuss